Successful Treatment of a Three-Column Thoracic Extension Injury with Recumbency - Choy, Winward (Cureus, 2016)
We report a unique instance of a 66-year-old male patient with an unstable three-column thoracic extension injury at the level of T4/5 who was treated with recumbency and bracing without surgery. A posterior long segment fixation was attempted three times on two separate occasions over the course of a week with failure due to difficulty in ventilating the patient during prone positioning, cardiopulmonary arrest, and hemodynamic instability during prone positioning for surgery. The decision then was to treat this fracture with recumbency. He was fitted with a thoracolumbosacral orthosis (TLSO), and was kept on bed rest for eight weeks. The patient’s activity was advanced to head of bed for 45 degrees for four weeks and then to 90 degrees for four other weeks. At his 16th week visit, the patient was asymptomatic, and a computer tomography (CT) scan and magnetic resonance imaging (MRI) of the thoracic spine demonstrated evidence of osteophyte bridging and restoration of normal alignment. Three-column thoracic extension injuries can be successfully treated with recumbency in poor surgical candidates.